Reward dan Pengambilan Keputusan Berdasarkan Persepsi Perawat dengan Perilaku Caring Perawat - Rini Mustamin; Zaenal Zaenal (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Caring is the most essential thing in nursing practice because caring is a dynamic approach that is closely related to the professionalism of nurses and lack of caring in nursing services can result in a decrease in the quality of nursing services, decreased patient satisfaction, and an increase in nursing days. The purpose of the study was to determine reward factors and decision making based on nurses' perceptions with nurses' caring behavior. This study used a correlational design in the form of cross sectional. The independent variable in this study is Reward and Decision Making and the dependent variable is caring behavior. The population in this study was all implementing nurses with non-probability sampling techniques, namely consecutive sampling with a total of 77 people in accordance with inclusion criteria and exclusion criteria. The results of the analysis showed a significant relationship between reward and decision-making with nurses' caring behavior (p = 0.000-0.030; α = 0.05). It can be concluded that organizational culture is related to nurses' caring behavior, not reward and decision-making even though there is a meaningful relationship. Follow-up approaches and research to determine the most dominant factors for nurses in nurses' caring behavior. All hypotheses are proven where there is a meaningful relationship of reward variables and decision making as part of organizational culture factors based on nurses' perceptions with nurses' caring behavior